Effect of sulphuric acid concentration on oil palm empty fruit bunch (EFB) to produce advanced carbon product - Siti Nurul Aishah, Ahmad Nordin (2012)
Oil palm empty fruit bunch (EFB) contains polymeric lignocellulosic component such as hemicellulose, cellulose and lignin and is therefore a potential raw material for producing advanced materials such as carbon electrode, and molecular sieve carbon. The parameters that have been focused throughout this experiment were concentration of acid sulphuric and temperature of carbonization. The experimental works has been done at GAS LABORATORY, Universiti Malaysia Pahang (UMP). In this research, the experiment has been run in slow pyrolysis process where empty fruit bunch (EFB) was pre-carbonized at 280 °C, then, it followed by grinding and sievingof the pre-carbonize EFB. Then carbon precursor was treated with 0.2M, 0.4M, and 0.6M of H2SO4 and was dried. The chemical changes of the treated EFB carbon precursor were discuses by using the thermogravimetric (TGA) analysis results. The green pellets are then prepare by mould compression of the carbon precursor powder and then will carbonize with 600°C, 800°C, and 1000°C of temperature by using multiple heating profile under nitrogen flow. Carbon pellet that prepared from 0.6 M of H2SO4 gave highest density (ρ). Air mixing and high temperature expose to the carbon pellet during carbonization process was affected the properties of carbon pellet, thus advanced carbon product such as carbon electrode and molecular sieve carbon can’t be prepared.